Nanoengineering Approaches to Tune Thermal and Electrical Conductivity of a BiSbTe Thermoelectric Alloy - Pakdel, Amir (My University, 2022)
Nanoengineering of thermoelectric (TE) materials is an effective approach todecouple their electronic and thermal transport properties, hence enhancing their TE efficiency. Nanoengineering strategies can significantly reduce the thermalconductivity through the corporation of different phonon scattering mechanisms,whereas the electrical conductivity may not be affected considerably. Herein, theeffects of three nanoengineering approaches on the structural, electrical, andthermal properties of Bi0.5Sb1.5Te3(BST) alloy are compared: (a) nanohybrid-ization of the alloy by adding Sb2O3nanoparticles, (b) severe plastic deformationvia high-pressure torsion, and (c) grain refinement by sonication of BST powdersbefore sintering. It is shown that among these methods, severe plastic defor-mation induces ultrafine grains and a high density of dislocations, resulting in alarge reduction of the total thermal conductivity (32.8%) and a moderate declinein the electrical conductivity of (15.7%) at 300 K. A notable decrease in the latticethermal conductivity (56.8% at 300 K) is attributed to midfrequency phononscattering by the dislocations together with low and high frequency scatteringsthrough grain boundaries and point defects, respectively. A new pathway isopened for designing highly efficient TE materials through nanoengineeringapproaches, particularly severe plastic deformation.
PUBLISHED
Keywords: thermoelectric (TE); Nanoengineering strategies; Bi0.5Sb1.5Te3(BST) alloy; thermoelectric (TE); Nanoengineering strategies; Bi0.5Sb1.5Te3(BST) alloy